Spiritual Dualism and The Christian Integrity Crisis: an Analogy of Dissociative Identity Disorder (DID) as a Theological-Ethical Study - Walui, Donny Ardo Eka Dharma Putra (Journal of Asian Orientation in Theology, 2025)
This study analyzes the phenomenon of inconsistent behavior in contemporary Christianity using Dissociative Identity Disorder (DID) as an analogical framework, with a primary focus on theological perspectives. The central issue examined is spiritual dualism, in which the spiritual identity displayed in church (spiritual and activist) contrasts with attitudes and actions outside of church (worldly). This dualism creates a crisis of credibility and validity in Christian witness that is vulnerable to challenge by the world. The research uses qualitative methods through a descriptive-analytical literature review approach to examine the gap between biblical normative standards (holiness and integrity) and empirical reality. The findings show that the main cause of this decline is compromise driven by the desire to be accepted by the world. The theological solution offered is a call for singular integrity that overcomes duality through consistency of faith and deeds (James 1:22). This is achieved through the revitalization of personal spiritual discipline and loving God above all else, in order to radiate distinctive holiness.To achieve this, we must develop a close relationship with God through prayer, worship, and quiet reflection at His feet. This will give us the strength to be sensitive to the things that God does not want and to love God above all else so that we are happy to do His will.